Social Return on Investment Program Pusaka Pangan Lokal (Puspaloka) Pt Pertamina Patra Niaga Fuel Terminal Rewulu - Alfiyansyah, Afiarta Akbar; Pramadha, Rezaldi Alief; Baskhara, Wisnu Eka; Wicaksono, Basuki; Pratiwi , Ayu (Jurnal Global Ilmiah, 2025)
This study aims to measure the value of Social Return on Investment (SROI) from the Local Food Heritage Program (PUSPALOKA) run by PT Pertamina Patra Niaga Fuel Terminal Rewulu in Padukuhan Bendo, Ngentakrejo Village, Kulon Progo Regency. This program is part of the implementation of Social and Environmental Responsibility (TJSL) in supporting community empowerment through improving the agricultural sector and food processing based on local potential. The research uses a qualitative approach with data collection techniques in the form of in-depth interviews from various stakeholders and the study of program documents. The analysis was carried out based on the SROI framework which includes five main stages, namely stakeholder identification, outcome identification, proof and value, impact determination, and calculation of social investment benefit ratio. The results of the study showed that the total benefits generated by the program reached IDR 231,939,744.30 compared to the total investment of IDR 82,329,760.07 resulting in an SROI ratio of 2.82. This means that every Rp1 social investment provides economic and social benefits of Rp2.82 for the community. The significant impact achieved by the program includes increasing agricultural productivity through the use of organic fertilizer Orgamin, saving production costs, working time efficiency, increasing women's income through the activities of the Subur Makmur Women Farmer Group (KWT), as well as strengthening social cohesion and community group capacity. In addition, there is a positive contribution to the environment through the reduction of organic waste and the absorption of carbon emissions. Overall, the results of the study confirm that the PUSPALOKA Program is not only socially feasible, but also contributes to sustainable development at the community level. Recommendations were submitted to strengthen the sustainability of the program through entrepreneurship training, marketing development, and business digitalization for the sake of community independence in the future.